Identification of the Barriers of Lean Construction Implementation in Construction Projects- A Review (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the current era of industrial and  enterprise evolution, time and resource are the fundamental  need of any industry. Utilizing the time and resource has  always been the primary goal of especially a construction  project in order to reduce the expenses, meet the project  deadlines and accomplish the work successfully. Lean  approach in the construction industry has been introduced  to facilitate and manage such procedure to achieve the  above-mentioned goals of a company. Construction  industry has also adapted this approach under the title of  lean construction to give boast in the process of  construction projects by applying the lean construction  techniques. In this research, we have tried to discover the  lean construction barriers in the construction industry and  limitations of implementing lean construction in  construction industry worldwide. The barriers have been  gathered through an extant literature survey and then  concluded by defining them among different categories of  professionals. It is concluded that overcoming the barriers  would lead to less wastage in the construction industry and  lead to more efficiency and productivity.
Keywords: Lean construction; barriers; construction; industry; construction projects